A New Kind Of Party Animal : How the Young Are Tearing Up the American Political Landscape - MITCHELL, Michele (Simon and Schuster, 1998)
A twenty-seven-year-old pundit explains the distinctive political orientation of America's young adults, outlining six key attributes, from lack of party affiliation to computer skills, that promise to transform the political landscape. 25,000 first printing. Tour.